Principals' and Teachers' Reports of Successful Teaching Strategies With Children With High-Functioning Autism Spectrum Disorder. (September 2017) - Stokes, Mark A.; Thomson, Mary; Macmillan, Caitlin M.; Pecora, Laura; Dymond, Sarah R.; Donaldson, Emma
Little research has been conducted on the evidence base for educational interventions implemented by teachers targeting students with high-functioning autism spectrum disorder (HFASD). Research examining particular techniques perceived as effective may facilitate guidelines for the application of evidence-based practices. A principal and teacher of students with HFASD from each of 29 different schools provided information on their current teaching interventions. Principals participated in an online survey designed to ascertain support for HFASD learners in their school, whereas teachers completed an online reflective journal to document methods they used in the classroom. Both teachers and principals found numerous strategies such as structure and incorporating needs to be successful. Inappropriate communication, disorganisation, and a lack of understanding were considered unhelpful. These results have implications for current practices in classrooms.